Internet‐based contingency management to promote smoking cessation: A randomized controlled study. Issue 4 (30th September 2013) - Dallery, Jesse; Raiff, Bethany R.; Grabinski, Michael J.
Abstract We evaluated an Internet‐based contingency management intervention to promote smoking cessation. Participants in the contingent group (n = 39) earned vouchers contingent on video confirmation of breath carbon monoxide (CO) ≤ 4 parts per million (ppm). Earnings for participants in the noncontingent group (n = 38) were independent of CO levels. Goals and feedback about smoking status were provided on participants' homepages. The median percentages of negative samples during the intervention in the noncontingent and contingent groups were 25% and 66.7%, respectively. There were no significant differences in absolute CO levels or abstinence at 3‐ and 6‐month follow‐ups. Compared to baseline, however, participants in both groups reduced CO by an estimated 15.6 ppm during the intervention phases. The results suggest that the contingency for negative COs promoted higher rates of abstinence during treatment, and that other elements of the system, such as feedback, frequent monitoring, and goals, reduced smoking.